Activated Carbon-Limestone-Alginate Beads for the Simultaneous Removal of Color and Turbidity of Kerian River - Zainol Abidin, Nurul Aini (International Journal of Integrated Engineering, 2019)
Activated carbon-limestone-alginate bead (ALA) was synthesized for the adsorption of color and turbidity of river water. This adsorbent was characterized using Scanning Electron Microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. Langmuir and Freundlich models were used for a mathematics description of the adsorption isotherm. The maximum adsorption capacity for color and turbidity obtained from Langmuir model were 0.446 PtCo/g and 5.155 NTU/g respectively. The equilibrium process was described well by the Freundlich isotherm model. Furthermore, the adsorption kinetics revealed that the adsorption process was successfully fitted with the pseudo-second-order kinetic model. All the results validated the feasibility of ALA for color and turbidity removal from river water.